2013
DOI: 10.3390/ijms140612411
|View full text |Cite
|
Sign up to set email alerts
|

Protein Folding and Aggregation into Amyloid: The Interference by Natural Phenolic Compounds

Abstract: Amyloid aggregation is a hallmark of several degenerative diseases affecting the brain or peripheral tissues, whose intermediates (oligomers, protofibrils) and final mature fibrils display different toxicity. Consequently, compounds counteracting amyloid aggregation have been investigated for their ability (i) to stabilize toxic amyloid precursors; (ii) to prevent the growth of toxic oligomers or speed that of fibrils; (iii) to inhibit fibril growth and deposition; (iv) to disassemble preformed fibrils; and (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
127
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(135 citation statements)
references
References 330 publications
(359 reference statements)
3
127
0
Order By: Relevance
“…Amyloidosis is a systemic disorder characterised by the deposition of aggregates of misfolded proteins in the brain or peripheral tissues [1,2]. These protein aggregates are known as amyloid fibrils; these are highly organised, generally insoluble and rich in b-secondary structure [3].…”
Section: Introductionmentioning
confidence: 99%
“…Amyloidosis is a systemic disorder characterised by the deposition of aggregates of misfolded proteins in the brain or peripheral tissues [1,2]. These protein aggregates are known as amyloid fibrils; these are highly organised, generally insoluble and rich in b-secondary structure [3].…”
Section: Introductionmentioning
confidence: 99%
“…One of the straightforward approaches to target amyloid-linked diseases and its associated medical complication is to find potential inhibitors against the onset of amyloid aggregation of proteins. Candidates ranging from single amino acids (Kar and Kishore 2007;Shiraki et al 2002;Ghosh et al 2009) and natural products (Stefani and Rigacci 2013) to selected peptides (Etienne et al 2006;Rajasekhar et al 2015;Viet et al 2011) have been reported to interfere with the amyloid aggregation of associated proteins. Few investigations Abstract Here, we have strategically synthesized stable gold (AuNPs Tyr , AuNPs Trp ) and silver (AgNPs Tyr ) nanoparticles which are surface functionalized with either tyrosine or tryptophan residues and have examined their potential to inhibit amyloid aggregation of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Amyloid diseases predominantly involve the aggregation of specific proteins, such as the prion protein or the amyloid β-peptide, but fibrils can be formed by many other peptides and proteins [3]. Natural phenolic compounds, a long family of plant substances, are one of the most actively investigated categories of potential amyloid inhibitors [4][5][6]. More than 8,000 plant polyphenols are currently known and more than 4,000 flavonoids have been identified among them [7].…”
Section: Introductionmentioning
confidence: 99%
“…The position of phenolic hydroxyl moieties on the aromatic rings is a major determinant of the potent anti-aggregation effect, while the number of hydroxyl groups is less important [12]. Natural phenolic and polyphenolic substances stabilize native states, or remodel and inactivate toxic amyloid oligomers [4]. Several observations suggest that polyphenols inhibit amyloid fibril formation through specific aromatic interactions with the amyloidogenic core [13].…”
Section: Introductionmentioning
confidence: 99%